Experimental Investigation of the Near Wake of a Pick-up Truck - Al-Garni, Abdullah M. (2003)
The results of an experimental investigation of the flow over a pickup truck are presented. The main objectives of the study are to gain a better understanding of the flow structure in near wake region, and to obtain a detailed quantitative data set for validation of numerical simulations of this flow. Experiments were conducted at moderate Reynolds numbers (~3×105) in the open return tunnel at the University of Michigan. Measured quantities include: the mean pressure on the symmetry plane, unsteady pressure in the bed, and Particle Image Velocimetry (PIV) measurements of the flow in the near wake. The unsteady pressure results show that pressure fluctuations in the forward section of the bed are small and increase significantly at the edge of the tailgate. Pressure fluctuation spectra at the edge of the tailgate show a spectral peak at a Strouhal number of 0.07 and large energy content at very low frequency. The velocity field measurements in the symmetry plane show that shear layers form at the top of the cab and the underbody flow region. The cab shear layer evolves more slowly than the underbody flow shear layer and does not interact strongly with the tailgate for the present geometry. Behind the tailgate there is no recirculating flow region in the symmetry plane believed to be due to downwash from streamwise vorticity in the near wake. There are small recirculating regions on the sides of the tailgate symmetry plane extending approximately one tailgate height downstream.